Taxonomy of theories for blockchain applications in business and management - Payam Hanafizadeh; Maryam Alipour (Digital Business, 2024)
The rising prominence of blockchain technology has spurred researchers to delve deeper into its applications through the lens of organizational and management theories. Our thematic analysis of blockchain literature reveals examination across five key areas: economic, strategic, operational, behavioral, and implementation considerations, each viewed through various theoretical perspectives. The multifaceted nature of blockchain phenomena necessitates diverse types of theory and research questions. Thus, the unique characteristics within each area stimulate the formulation of inquiries that address a system of research questions about what, how, why, when, where, what will be, and how to do. Existing literature predominantly emphasizes explanatory and predictive type of theories, notably expanding research topics such as blockchain adoption behavior. However, this singular focus limits the exploration of diverse reasoning approaches suited to blockchain's complexity. Our study illustrates how different types of theory contribute to understanding each of the identified blockchain application areas. Based on our findings, we propose pertinent questions that highlight the need for varied theoretical frameworks and address specific issues within each application area. Furthermore, we recommend appropriate type of theories to address these questions, fostering a more multi-perspective investigation across the breadth of blockchain-related research topics and areas. By embracing diverse theoretical perspectives, we aim to create a more balanced research landscape, facilitating deeper insights into blockchain phenomena.
Keywords: 650; Blockchain applications; Management theory; Organizational theory; Theory taxonomy